2004
DOI: 10.1007/s10310-004-0088-9
|View full text |Cite
|
Sign up to set email alerts
|

Leaf-litter decomposition of 15 tree species in a lowland tropical rain forest in Sarawak: dynamics of carbon, nutrients, and organic constituents

Abstract: The effects of tree species on the dynamics of nutrient transformations during leaf-litter decomposition are not well understood in tropical rain forests. To examine differences in the dynamics of C, nutrients, and organic constituents during decomposition among tree species, the leaf-litter decomposition of 15 trees was assessed using a litter-bag method in a lowland tropical rain forest in Sarawak. The dynamics of C was parallel to that of weight loss. The dynamics of nutrients were grouped into three patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
4
22
1
2
Order By: Relevance
“…This in turn highlights the role of surface runoff in the elution and transport of chemicals. Our finding is contradictory to some other studies in which a relatively slow release of nutrients from plant detritus has been observed (Hongve, 1999;Hirobe et al, 2004). However, the cited studies involved only fresh plant detritus which releases N, P and other elements slowly during its gradual decomposition.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This in turn highlights the role of surface runoff in the elution and transport of chemicals. Our finding is contradictory to some other studies in which a relatively slow release of nutrients from plant detritus has been observed (Hongve, 1999;Hirobe et al, 2004). However, the cited studies involved only fresh plant detritus which releases N, P and other elements slowly during its gradual decomposition.…”
Section: Discussioncontrasting
confidence: 99%
“…The chemical properties of runoff may vary significantly and depend, inter alia, on catchment area properties such as geomorphology, vegetation and the degree of human impact. In forest ecosystems, the input and output of essential nutrients is relatively small when compared to their total amount of cycling within the system (Hirobe et al, 2004). However, the elements exported from wooded catchments may have a considerable impact on the quality of surface waters (Irfanullah, 2009;Park et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ca from litterfall is likely to stay longer on the forest floor than other elements. During litter decomposition in a primary forest in Borneo, Ca remained at almost 100% on a mass basis over a period of a few months in some species, but the process differed by species and litter characteristics (Hirobe et al 2004).…”
Section: Effect Of Element Flux In Litterfall On Soil Chemistrymentioning
confidence: 99%
“…Urban runoff, in turn, can contain significant concentrations of persistent contaminants such as oil derivates, heavy metals and polycyclic aromatic hydrocarbons, leading to contamination of municipal surface waters (Choe et al 2002;Azizuddin et al 2014;Rzymski et al 2014). In forest ecosystems, it is claimed that the output of nutrients is relatively small when compared to their total amount cycling within the system (Hirobe et al 2004). However, the elements exported from the wooded catchments may still have considerable impact on the quality of receiving waters (Strobel et al 2001;Vuornenmaa et al 2002;Astrom et al 2004;Park et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The potential role of surface runoff in increasing the trophy of water bodies was also indicated (Klimaszyk and Rzymski 2011). It is likely that different types of forest litter, coniferous, mixed and deciduous, may have a different impact on the chemistry of runoff due to varying quantities of chemical compounds in litter produced by different tree species (Klimaszyk and Rzymski 2011;Hirobe et al 2004). For example, higher levels of phosphorus and nitrogen are leached from deciduous litter, while coniferous litter is usually richer in organic matter and humic acids (Klimaszyk andRzymski 2011, 2013).…”
Section: Introductionmentioning
confidence: 99%